Themes of Love and Solitude in Contemporary Azerbaijani Women’s Prose - S. E. Tarverdiyeva (Научный диалог)
The article examines the representation of themes of love and loneliness in women’s prose in Azerbaijan. It is noted that the literary works of women in different countries have gained particular relevance at the end of the 20th and beginning of the 21st centuries. The novelty of the research lies in identifying key themes raised in the works of several leading Azerbaijani female writers, who are not well known to a wide circle of Russian readers. The creative works of A. Masud, Farida, and A. Gyulnel are analyzed, with themes of love and loneliness being the focus of the study. It has been established that the thematic content of the works exhibits a traditional character typical of women’s prose: the quest for love by women and men, contemplation of issues of loyalty and betrayal, and solitude. It is shown that the characters in their pursuits do not find understanding from those around them. The absence of love drives A. Masud’s characters to madness (“Fatima” novel), physical death (“Aysun” story), or moral decline (“The Boss” story). In Farida’s work “Silent Birds”, the issue of the influence of ancient cruel traditions on the relationships and fate of young people is raised. In “Cactus” by A. Gyulnel, the heroine suffers from loneliness due to the lack of parental love. The author concludes that the variety of issues raised by female authors is imbued with the idea of the tragedy of human existence without love.